Assessment of health related quality of life (HRQol) in patients with Meige’s syndrome - Verma, Alok; Singh, Pavan; Agarwal, Saurabh; Gupta, Babita (International Journal of Research in Medical Sciences, 2018)
Background: There is paucity of literature regarding health related quality of life (HRQoL) in Meige’s syndrome (MS) especially from India. This study assessed HRQoL in its global and disease specific aspect by previously validated instruments in patients with Meige’s syndrome. Methods: The study was performed in AIIMS, New Delhi. Subjects with Meige’s syndrome as well as age and gender matched healthy controls were enrolled from Movement Disorder and botulinum toxin clinic, Department of Neurology, AIIMS, New Delhi. Uneducated patient, those could not read questionnaires and cases who had received botulinum toxin within 6 months were excluded from the study. Results: A 14 pts of Meige’s syndrome were enrolled and 14 age matched controls were taken. All the pts of Meige’s syndrome scored worse in SF-36 as compared to controls in areas of role physical (p =0.002), bodily pain (p = 0.001), general health (p = <0.001), social functioning (p = 0.05) and role emotion (p = <0.001). 50% of patients with Meige’s syndrome had depression out of whom 21.4 % had moderate depression. Patients with Meige’s syndrome had significantly impaired scores in 10 of the 12 subscales which was profound in areas of ocular pain, near activities, distance activities, social functioning, role difficulties, dependency, driving, compared to borderline impairment in general vision, mental health, color vision. Conclusions: This study clearly demonstrated that pts with Meige’s syndrome, suffered from significant impairment in HRQoL as compared to controls. Higher proportion of patients with Meige’s syndrome suffered from moderate depression compared to their control. Pts with Meige’s syndrome had severe impairment of vision related quality of life.